The Judge's Estimation Power in Giving the Judicial Term in the Execution Case: comparative study - الخالدي, حميد سلطان; حمود, لؤي سطام (Journal of Legal Sciences, 2019)
The judge's estimation power in giving the judicial term in the execution case is represented in the possibility of amending the term of the contract commitment. That term on which both parties agreed to execute the contract commitment at its due date, because at the due date of fulfilling the commitment the debtor is bounded to pay, yet this fulfillment may be exhausting to the debtor, or causing him damage or harm more than that damage caused to the creditor in delaying the fulfillment.                                              The judge enjoys a wide estimation power during his considering the execution case laid before him, in giving the debtor who violated his commitment a judicial term in order to fulfill his commitment, or not giving him, as the judge may estimate that the debtor's non-fulfillment of his commitment, or his delaying it is due to reasons against his will, and that these reasons may vanish after a short time, or that this delay is for a short time and caused no great damage or harm to the creditor; thus the judge finds himself motivated to give the debtor a judicial term by which he fulfills his commitment, under the impulse of justice and the wish to keep the contracting relations as much as possible.